Women’s experiences of and satisfaction with childbirth: Development and validation of a measurement scale for low- and middle-income countries - Meghan A. Bohren; Charbel Abi Saad; Charles Kaboré; Kristi Sidney Annerstedt; Claudia Hanson; Myriam de Loenzien; Simon Tiendrebeogo; Fadima Bocoum; Marion Ravit; Camille Etcheverry; Pisake Lumbiganon; Nampet Jampathong; et al. (PLoS ONE, 2025)
Background Measuring person-centered maternity care outcomes typically consists of two types of measures: experiences of care and satisfaction with care. There are limited validated measurement tools for these measures, particularly in low- and middle-income countries (LMICs). The QUALI-DEC study aims to improve decision-making around caesarean section. We describe development of the QUALI-DEC Study Birth Experience and Satisfaction (QD-BES) scale, and scale validation in Argentina, Burkina Faso, Thailand, and Viet Nam. Methods We used a three-phase scale development and validation approach: 1) item development, 2) scale development, and 3) scale evaluation. We systematically identified existing tools, and assessed them using the QUALI-DEC theory of change, study context, and psychometric qualities. We proposed the 10-item QD-BES scale to balance feasibility, theoretical coverage, and comprehensiveness. We conducted a baseline exit survey with post-partum women in 32 hospitals in 4 countries. We conducted exploratory factor analysis (EFA), and confirmatory factor analysis (CFA). Results 3127 women participated, most were multiparous (61.0%), without previous caesarean section (77.2%), and preferred vaginal birth (72.8%) despite high rates of caesarean section (39.4%). EFA identified three dimensions: emotional satisfaction (3-items), support and respect by providers (4-items), and communication with providers (3-items), with high loading coefficients (0.5–0.97). CFA confirmed the three-dimension scale, with good model fit (CFI and IFI: 0.95, Cronbach’s alpha: 0.70–0.90). Criterion validity was assessed by exploring characteristics of women, obstetric histories, and birth experiences. Conclusions We present psychometric validation of a scale measuring women’s satisfaction with care and experiences of childbirth care, using a systematic approach to development and validation in four LMICs. The 10-item QD-BES-scale is short, easily-administered, valid, and reliable. The QD-BES-scale is useful to contribute to the generation of new knowledge about quality of maternity care in LMICs, as well as help to meet the major challenge of implementing and measuring respectful care at scale.